2020
DOI: 10.1128/mbio.00126-20
|View full text |Cite
|
Sign up to set email alerts
|

Key Positions of HIV-1 Env and Signatures of Vaccine Efficacy Show Gradual Reduction of Population Founder Effects at the Clade and Regional Levels

Abstract: HIV-1 group M was transmitted to humans nearly one century ago. The virus has since evolved to form distinct clades, which spread to different regions of the world. The envelope glycoproteins (Envs) of HIV-1 have rapidly diversified in all infected populations. We examined whether key antigenic sites of Env and signatures of vaccine efficacy are evolving toward similar or distinct structural forms in different populations worldwide. Patterns of amino acid variants that emerged at each position of Env were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Kumar et al 2018a). The trimeric Env glycoproteins on the virus surface are the most diverse of all proteins encoded by HIV-1; which differs by greater than 20% of amino acids between matched subtype (Gnanakaran et al 2007; Han et al 2020; Hraber et al 2014; Korber et al 2001; Lynch et al 2009) and which continues to diversify at a population level (Bouvin-Pley et al 2013; Bunnik et al 2010; DeLeon et al 2017; Hraber et al 2014). This has been substantiated by observation that several epitopes that are targeted by different bnAbs those have been found to vary over time (DeLeon et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al 2018a). The trimeric Env glycoproteins on the virus surface are the most diverse of all proteins encoded by HIV-1; which differs by greater than 20% of amino acids between matched subtype (Gnanakaran et al 2007; Han et al 2020; Hraber et al 2014; Korber et al 2001; Lynch et al 2009) and which continues to diversify at a population level (Bouvin-Pley et al 2013; Bunnik et al 2010; DeLeon et al 2017; Hraber et al 2014). This has been substantiated by observation that several epitopes that are targeted by different bnAbs those have been found to vary over time (DeLeon et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In different populations worldwide infected by virus from the same HIV-1 clade, each Env position exhibits a similar frequency distribution of amino acids (13). In many cases, founder effects of substitutions in monophyletic lineages are reduced by evolution of the position toward the clade-specific frequency distribution.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that in distinct geographic regions, each Env position has evolved toward a specific frequency distribution of amino acids that replaced the regional ancestral form. The frequency distribution is specific for HIV-1 clade and is similar in monophyletic and paraphyletic lineages, suggesting that, at a population level, Env encounters similar selective pressures (13).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations